From Seers to Sen: The meaning of economic development - E. Wayne Nafziger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The paper compares perspectives on the meaning of development in the late 1970s and early 1980s to the contemporary period, with a focus on the works of Dudley Seers and Amartya Sen. Both men were critical of the development literature of their times. Seers was especially critical of neoclassicism's universal claims and economic growth as the prime objective. For Sen, development involves reducing deprivation or broadening choice. One challenge for future work is for development economists, similar to Seers and Sen, to be more holistic, integrating economic development, human rights, and conflict reduction. – inequality ; poverty ; employment ; growth ; neoclassicism ; entitlement ; famine
Keywords: B2; O1; 330; Entwicklungstheorie